Life and Ethics - Donatelli, Piergiorgio (Itinerari, 2023)
In this paper, I will deal with the notion of form of life, specifically in relation to the domains of freedom and autonomy. I will compare and contrast the positions of those who reject the concept of form of life in order to account for freedom and autonomy (e.g. Peter Singer) with those who appeal to a form-of-life-view in order to establish the traditional understanding of the spheres of life (Anscombe). Differing from both kinds of positions, I will suggest that we should appeal to forms of life in order to account for freedom and autonomy: freedom and autonomy have been conceived as formed ways of living, as initiations of living beings into social and cultural spaces (McDowell). Forms of life should not be thought of though as the successful initiation of our natural being in the realm of second nature. Rather, they are best described as the domestication of the vulnerabilities of life which leave their form impressed on the habits and the natural rhythms of life: this is argued especially following Stanley Cavell’s lead.